A review of the historical use and criticisms of gait analysis evidence. Issue 4 (July 2018) - Nirenberg, Michael; Vernon, Wesley; Birch, Ivan
Abstract: The use of gait analysis is a well-established facet of practice for many professions and a fundamental aspect of clinical practice. In recent times, gait analysis evidence has emerged as a new area of forensic practice. As its use has continued to spread and develop, the area of work has come under close scrutiny and subsequent criticism. The purpose of this paper is to examine the historical use of gait analysis evidence and consider the criticisms of this work. Through the use of the historical records of cases within the public domain it has been determined that gait analysis as evidence was first presented in court over 175 years ago, although it has only been utilized by experts in more recent times. The quality of analysis underpinning such evidence has been variable, and has been undertaken by both non-expert and expert witnesses. The work undertaken by expert witnesses appears to have been both non-scientific and scientific in nature, though there is limited reporting of cases involving scientific approaches. Given the variation in the quality of the methodologies utilized, there is the potential for confusion within the courts, where it may be difficult for the judge or jury to determine the appropriate weight that can be attributed to the evidence. It is concluded that future publications should explore the scientific basis of forensic gait analysis to evaluate standards, reliability and validity, as well as reporting the methodologies utilized in relevant cases in the field. It is also recommended that courts consider in greater depth an expert's theoretical approach and experience prior to admitting their evidence. The publication of 'Forensic gait analysis: a primer for courts', although limited in some aspects of its consideration of practice, is a welcome addition to the information available for guidance. Highlights: Gait analysis dates back to Aristotle (384–322 BCE). Gait has been presented in court as evidence since at least 1839. Potential for confusion within the courts More research publications are required. Greater consideration of expert's approach and experience is required.